Effect of cycling specialization on effort and physiological responses to uphill and flat cycling at similar intensity - Gandia Soriano, A.; Carpes, F. P.; Rodríguez Fernández, A.; Priego-Quesada, J. I. (European Journal of Sport Science, 2021)
Power output is considered one of the best tools to control external loads in cycling, but the relationship between a target power output and the physiological responses may suffer from the effects of road gradient, which is also affected by cyclist specialization. The objective was to determine the effects of cyclist specialization on effort perception and physiological response (heart rate and lactate concentration) while sustaining efforts at similar power output but riding on two different road gradients. Nineteen male competitive road cyclists performed two randomized trials of 10 min at 0% (velodrome) and 10 min at 6% road gradient (field uphill), at an intensity of 10% ± 3% below the individual`s functional threshold power. Cadence was kept between 75 and 80 rpm in both trials and posture remained unchanged during the tests. Heart rate, speed, cadence, power output, blood lactate, and rate of perceived effort were measured for each trial. K-means cluster analyses differentiate uphill (n = 10) and flat specialists (n = 9) according to lactate responses. Flat specialists presented lower heart rate (p < 0.001 and ES = 0.2), perceived exertion (p < 0.01 and ES = 0.7), and blood lactate concentration (p < 0.001 and ES = 0.7) riding on the flat than uphill. Uphill specialists presented lower perceived exertion (p < 0.01 and ES = 0.8) and blood lactate concentration (p < 0.01 and ES = 0.5) riding uphill than on the flat. In conclusion, the combination of cyclist specialization and road gradient affects physiological and effort perception parameters in response to a similar power output demand. These factors deserve attention in training schedules and monitoring performance using power output data.